Italian youth mobility: The case for a Mediterranean model of ‘family-centred’ mobile transitions - Marchetti, Giulia; Baldassar, Loretta; Harris, Anita; Robertson, Shanthi (Ethnicities, 2022)
This article seeks to advance our understanding of contemporary transnational youth mobility, drawing on the concept ‘mobile transitions’ to explore scholarly approaches to the mobility practices of young Italians moving abroad. We present a critical literature review of the intersections of migration, youth and transition studies to argue that the literature on youth transnational mobility currently features two contrasting models comprising a ‘transitions-focused’ Global South model and an ‘experiential-focused’ Global North model. This bifurcation fails to account for emergent regional models of mobility that may help to sharpen scholarly understandings of a new generation of youth ‘on the move’. We propose an alternative model positioned somewhere along the spectrum between the Global North and Global South models, which we define as the Mediterranean model of ‘family-centred’ transnational youth mobility. This model reflects aspects of both privileged, experiential youth migrations, which tend to undervalue the impact on transitions to adulthood, and economically driven youth migrations, which tend to focus more directly on the economic dimensions of youth to adulthood transitions. The Mediterranean model highlights more broadly how mobility enables and shapes transitions, which are simultaneously driven by both economic imperatives and individual experiential desires, and mediated through family and culture.